Establishing and Sustaining SoTL: The Role of Brokering and Strategic Leadership (Teaching and Learning Inquiry, 2025)
Although the scholarship of teaching and learning (SoTL) has continued to evolve as a field, building and sustaining SoTL within educational institutions remains challenging. Through interviews with 18 SoTL scholars, we sought to examine the question, “How do individuals and institutions sustain SoTL?” Our findings highlighted the important roles of brokering and strategic leadership. Using the landscape of practice as our theoretical framework, we identified the many ways that SoTL scholars influence and are influenced by these roles. SoTL practices are undeniably vulnerable to fluctuating institutional agendas and discourses, changes in leadership, funding opportunities, formal rewards, and overt recognition of SoTL, including scholars’ positions and titles. We found institutional actions may be critical in launching SoTL, supporting it at different times, or establishing academic positions for SoTL scholars who are able to promote the field. However, institutional support waxed and waned across institutions, with a few exceptions, which meant that the SoTL brokers working across the landscape of practice sustained SoTL over time through their strategic leadership. Despite varying contexts, our participants were in it for the long haul, brokering their connections to withstand the vagaries of institutional support. Thus, building SoTL is a long-term effort that requires resilience and a certain degree of institutional support, but more importantly, sustained, bottom-up support for faculty development, collaboration, and commitment across the landscape of practice.